1999
DOI: 10.3750/aip1999.29.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet composition on the levels of glucose, lipids, and lipoproteins of the blood and on the chemical composition of two-year-old carp (Cyprinus carpio L.) reared in cooling waters

Abstract: The present study was conducted on two-year-old carp, reared in the production-scale conditions. The fish were kept for 62 days in cooling water and fed feeds differing in the fat content (35.9% of the energetic value of the diet) and carbohy drate content (35.6% of the energetic value of the diet). The experiment resulted in statistically significant differences in the levels of glucose, lipids, and blood lipoproteins as well as in the body composition of the fish in relation to the pre-experiment values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Dwiema skrajnymi zawartościami wody (minimalną i maksymalną) charakteryzowały się mięśnie ryb pochodzących z województw północnych (Hodowla "W-M", oraz Hodowla "K-P"), dlatego też można przypuszczać, że położenie geograficzne hodowli ryb nie wpływa na zawartość suchej masy w ich mięsie. Według Friedrich i Stepankowskiej [7] zawartość wody w mięsie karpia hodowlanego kształtuje się na poziomie 72 -73 %, w innych publikacjach te same autorki [8] podają przedział 69 -70 %. Z kolei Memon i wsp.…”
Section: Wyniki I Dyskusjaunclassified
“…Dwiema skrajnymi zawartościami wody (minimalną i maksymalną) charakteryzowały się mięśnie ryb pochodzących z województw północnych (Hodowla "W-M", oraz Hodowla "K-P"), dlatego też można przypuszczać, że położenie geograficzne hodowli ryb nie wpływa na zawartość suchej masy w ich mięsie. Według Friedrich i Stepankowskiej [7] zawartość wody w mięsie karpia hodowlanego kształtuje się na poziomie 72 -73 %, w innych publikacjach te same autorki [8] podają przedział 69 -70 %. Z kolei Memon i wsp.…”
Section: Wyniki I Dyskusjaunclassified
“…However, one cannot exclude a possibility that a higher albumin content in Group II was related to the albumin function to bind different ligands in blood, including free fatty acids (FF A). Earlier studies demonstrated the high triacylglycerol levels in fish fed carbo hydrate-rich diet to enhance the blood FF A levels (Friedrich and Stepanowska 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The study results on the Neil tilapia (Oreochromis niloticus), northern Mediterranean Sea fish, catfish of the Atatürk Lake in Turkey, whitefish and the pompous fishes (Friedrich and Stepanowska, 1999;Mohamed et al, 2010). The results of this study are based on the lowest absorption and concentration of heavy metals in the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The high dispersion of heavy metals on the ground, their various uses, and especially the toxic properties of these heavy metals, have caused this group of metals to become one of the most important environmental pollutants. On the other hand, industrial waste, geochemical structure and, mining of metals are the potential sources of heavy metal contamination in the aquatic environment (Friedrich and Stepanowska, 1999). These heavy metals are divided into two classes, transition metals and, metalloids.…”
Section: Introductionmentioning
confidence: 99%